Menggali Nilai-Nilai Kearifan Lokal Dalam Tradisi Kumpul Sanak di Rengas Bandung Kabupaten Muaro Jambi - Ramadani, Anggina; Novelmi, Dian; Rahma, Dwi; Mashuro, Mashuro (CV. Rayyan Dwi Bharata, 2025)
This study presents a bibliometric analysis of studies that focus on the concept of independent learning in Indonesia in the period 2015-2025. Through the collection and analysis of Google Scholar database data, this study identifies research development trends, emerging main themes, and collaboration patterns between researchers. This study uses the Publish or Perish reference manager application to retrieve the Google Scholar database in order to fulfill research data and the VOS viewer application is used to visualize and evaluate future directions in research. The results show 500 relevant articles. The results of the analysis show an increase in the number of publications over time, with a primary focus on aspects such as school autonomy, student participation, learning innovation, and policy evaluation. These findings provide a deeper understanding of the contribution of research to Exploring Local Wisdom Values in the Kumpul Sanak Tradition.